Gamete co-incubation duration modulates blastocyst developmental competence in buffalo through regulation of growth factors, steroidogenesis and oxidative stress pathways - Garbhit Sharma; Anand Kumar Pandey; Hitesh Jangra; Sandeep Kumar; Pradeep Saini; Rajesh Kumar; Divya Choudhary (Molecular Biology Reports, 2026)

Assessment of design challenges and viability of wireless electric vehicle charging stations in residential setup to empower sustainable e-mobility: A comprehensive review - Anubhav Kumar Pandey; Nandini K․ K․; Suvetha P S; Abhinandan S Marashiddannavar; Divya Jaganath; Chandana Govindanayak; Anand Reddy (Next Research, 2026)

Chemical and biological cargo on microplastics: current evidence for the Trojan-horse pathway to human exposure - Saurabh Singh; Varsha Tripathi; Pallavi Srivastava; Divya Pandey; Archana Roy; Mika Sillanpää (Environmental Research, 2026)

Identification and validation of natural product-based KRASG12D inhibitors through structure-based virtual screening, molecular dynamics simulation, and in vitro studies - Divya Pandey; Shubham Dwivedi; Kuldeep K. Roy (Molecular Diversity, 2026)

District-Level Groundnut Yield Prediction in Gujarat State Using Machine Learning and Remote Sensing Data - Drashti Nayakpara; Divya Prajapati; Kamal Pandey; N. R. Patel (Journal of the Indian Society of Remote Sensing, 2026)

Influence of Plant Growth Regulators on Growth, Yield and Fruit Quality of Strawberry Cv. ‘Camarosa’ Under Protected Conditions - Suman Bodh; Jitender Kumar Chauhan; Gopal Singh; Meera Devi; Divya Pandey (Applied Fruit Science, 2026)

Role of elicitors in secondary metabolites production in Glycyrrhiza glabra L., a highly valued medicinal plant - Divya Jaiswal; Akash Hindangmayum; Devendre Kumar Pandey; Kandregula Sowjanya Sree; Padmanabh Dwivedi (The Nucleus, 2026)

Soft computing techniques for atmospheric pollution and traffic emission prediction - Vivek Mathur; Divya Srivastava; Jaya Pandey; Vivek Mishra (Environmental Modelling & Software, 2026)

Integrated cytotoxicity screening and in silico analysis of coumarin nucleoside conjugates as computationally modeled VEGFR-2 inhibitors: oncocyte cytotoxicity, molecular docking, and dynamics simulation studies - Divya Mathur; Vipin K. Maikhuri; Sushma Yadav; Nidhi Bhardwaj; Shreya Pandey; Hangshika Sharma; Meenakshi Thakur; Alok Chandra Bharti; Debdip Bhandary; Anna Senrung (In Silico Pharmacology, 2025)

Harnessing genetic diversity and heterosis in basmati rice for biofortification and yield improvement - Basu Sudhakar Reddy; Dinesh Chandra Baskheti; Indra Deo Pandey; Divya Chaudhary; Sahar Osman A. Ali; Mohammad Raish; Suhail Ashraf (Journal of Crop Science and Biotechnology, 2025)

Quercus leucotrichophora strategies to adapt the different environments in Western Himalaya - Pooja Negi; Deep C. Tiwari; Monika Rawat; Shinny Thakur; Divya Khatri; Rajiv Pandey; I. D. Bhatt; Sunil Nautiyal (Plant Ecology, 2025)

Emphasizing the role of wheat circular RNA in defense response against stripe rust disease - Divya Chauhan; Dwijesh Chandra Mishra; Priyanka Balley; Jyotika Bhati; Himanshu Pandey; Suphiya Khan (Journal of Plant Biochemistry and Biotechnology, 2025)

Phase equilibria modelling, fluid inclusion study, and U-Pb zircon dating of ultra-high temperature mafic granulites from Rampur domain, Eastern Ghats province: implications for the Indo-Antarctic correlation - Divya Prakash; Rajeev Kumar Pandey; Saurabh Singh; Chandra Kant Singh; Manish Kumar; Bikash Mahanta; Aditya Kharya; Himanshu K. Sachan; Kamesh Sharma (Contributions to Mineralogy and Petrology, 2025)

Allometric scaling and carbon sequestration in agroforestry species of the Western Himalayas: a model-based approach - Megha VR; R. Kaushal; Sadikul Islam; Uday Mandal; Harsh Mehta; Rajkumar; J. M. S. Tomar; Anand Kumar Gupta; Anupam Barh; Vishwal Madhav P; Vibha Singhal; Rajiv Pandey; et al. (Environmental Monitoring and Assessment, 2025)

Ultrahigh-temperature granulites from the Shillong-Meghalaya Gneissic Complex, NE India: Implications for the Indo-Antarctic Correlation - Bikash Mahanta; Divya Prakash; Manish Kumar; Saurabh Singh; Rajeev Kumar Pandey; Chandra Kant Singh; Roopali Yadav; Jesus Solé Vinas (Journal of Asian Earth Sciences, 2025)

Investigation of Trifolium repens L. from the Indian Himalayan region as a phyto-therapeutic agent - Leirika Ngangom; Divya Venugopal; Neha Pandey (Natural Product Research, 2024)

Impact of urbanization and temperature on local abundance of Drosophila repleta Wollaston (1858) in the Western Himalayas - Seema Ramniwas; Girish Kumar; Manish Pandey; Divya Singh (Journal of Asia-Pacific Entomology, 2024)

CMIP6 Model Evaluation for Mean and Extreme Precipitation Over India - Prabha Kushwaha; Vivek Kumar Pandey; Prashant Kumar; Divya Sardana (Pure and Applied Geophysics, 2024)

Drought stress in maize: stress perception to molecular response and strategies for its improvement - Ashutosh Singh; Himanshu Pandey; Saurabh Pandey; Dalpat Lal; Divya Chauhan; Aparna; Suresh H. Antre; Santhosh B; Amarjeet Kumar (Functional & Integrative Genomics, 2023)

Differential expression of the AP2/EREBP gene family in the contrasting genotypes of maize provides insights of abiotic stress tolerance - Manisha Kumari; Saurabh Pandey; Divya Chauhan; Himanshu Pandey; S. Divakar; Khemraj Meena; Ashutosh Singh (Cereal Research Communications, 2023)

Linking the role of melatonin in plant stress acclimatization - Ashutosh Singh; Himanshu Pandey; Apurba Pal; Divya Chauhan; Saurabh Pandey; Dinkar J Gaikwad; Chandrasekhar Sahu; Kousik Atta (South African Journal of Botany, 2023)

Soil and Ocean Carbon Sequestration, Carbon Capture, Utilization, and Storage as Negative Emission Strategies for Global Climate Change - Divya Pant; Kabita Kumari Shah; Sadikshya Sharma; Maya Bhatta; Subina Tripathi; Hari Prasad Pandey; Himanshu Tiwari; Jiban Shrestha; Ashbin Kumar Bhat (Journal of Soil Science and Plant Nutrition, 2023)

A comprehensive health effects assessment of the use of sanitizers and disinfectants during COVID-19 pandemic: a global survey - Fallah Hashemi; Lori Hoepner; Farahnaz Soleimani Hamidinejad; Daniela Haluza; Sima Afrashteh; Alireza Abbasi; Elma Omeragić; Belma Imamović; Narin A. Rasheed; Taqi M. J. Taher; Fitri Kurniasari; Dhuha Youssef Wazqar; et al. (Environmental Science and Pollution Research, 2023)

What regulates the rhizodeposition of winter oilseed rape during growth? - Rainer Remus; Divya Pandey; Dietmar Lüttschwager (Plant and Soil, 2022)
Purpose The goal of this work was to contribute to a better understanding of the process of rhizodeposition in crops and to find helpful approaches for creating a simple model of rhizodeposition. For this purpose, we tested three hypotheses about the relationships and changes in the relative C partitioning coefficients and their ratios. In particular, we analyzed the relationships between root growth, belowground respiration, rhizodeposition and other traits during plant growth. Methods The ranges of variation in $$^{14}$$ 14 C partitioning coefficients and various plant traits were determined after $$^{14}$$ 14 C labeling of four winter oilseed rape genotypes in three developmental stages. Result For all genotypes, we found very strong and significant correlations between the percentages of freshly assimilated C used for rhizodeposition and root growth. In addition, we showed that the ratios of the relative $$^{14}$$ 14 C fluxes in the root-soil-soil gas system changed significantly during plant development and that the relative and absolute C fluxes of rhizodeposition followed different trends. The root growth rate and the change in the ratio of the percentages of $$^{14}$$ 14 C in rhizodeposition and root tissue over time were the key factors that determined the absolute amount of rhizodeposited C. We also found that the C partitioning in a taproot system leading to root growth and rhizodeposition was similar to that of an adventitious root system. Conclusion Based on our results, we conclude that using the identified key factors in combination with a root growth model, a simple model can be generated to describe rhizodeposition.

Can the nation-wide COVID-19 lockdown help India identify region-specific strategies for air pollution? - Md Najmus Saadat; Sujit Das; Senjuti Nandy; Divya Pandey; Monojit Chakraborty; Usha Mina; Abhijit Sarkar (Spatial Information Research, 2022)

Epigenetics and epigenomics: underlying mechanisms, relevance, and implications in crop improvement - Gaurav Agarwal; Himabindu Kudapa; Abirami Ramalingam; Divya Choudhary; Pallavi Sinha; Vanika Garg; Vikas K Singh; Gunvant B Patil; Manish K Pandey; Henry T Nguyen; Baozhu Guo; Ramanjulu Sunkar; et al. (Functional & Integrative Genomics, 2020)

A Novel Hybrid Feature Selection Model for Classification of Neuromuscular Dystrophies Using Bhattacharyya Coefficient, Genetic Algorithm and Radial Basis Function Based Support Vector Machine - Divya Anand; Babita Pandey; Devendra K. Pandey (Interdisciplinary Sciences: Computational Life Sciences, 2018)

Electrophoretic Separation of Humic Acids Isolated from Tropical Soils Through Modified Denaturing Polyacrylamide Gel Electrophoresis - Divya Pandey; Abhijit Sarkar; S. B. Agrawal; Madhoolika Agrawal (Agricultural Research, 2017)

Overexpression of hsp27 Rescued Neuronal Cell Death and Reduction in Life- and Health-Span in Drosophila melanogaster Against Prolonged Exposure to Dichlorvos - Ashutosh Pandey; Sanjay Saini; Rehana Khatoon; Divya Sharma; Gopeshwar Narayan; Debapratim Kar Chowdhuri (Molecular Neurobiology, 2016)

Greenhouse Gas Fluxes from Sugarcane and Pigeon Pea Cultivated Soils - Divya Pandey; Madhoolika Agrawal (Agricultural Research, 2015)

Biomarker System for Genetic Analysis of Stored Grain Pests Callosobruchus maculatus and Callosobruchus chinensis - Divya Pandey; Bharat Neekhra; Meeta Mishra; Smita Banerjee; Subodh Kumar Jain (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2015)

Traditional uses of medicinal plants for dermatological healthcare management practices by the Tharu tribal community of Uttar Pradesh, India - Akhilesh Kumar; Vimal Chandra Pandey; Anant Gopal Singh; Divya Darshan Tewari (Genetic Resources and Crop Evolution, 2013)

Comparative Evaluation of Oral Administration of Probiotic Lactobacilli-fermented Milks on Macrophage Function - Rajeev Kapila; Suman Kapila; Meena Kapasiya; Divya Pandey; Ajay Dang; Vamshi Saliganti (Probiotics and Antimicrobial Proteins, 2012)

Documentation and determination of consensus about phytotherapeutic veterinary practices among the Tharu tribal community of Uttar Pradesh, India - Akhilesh Kumar; Vimal Chandra Pandey; Divya Darshan Tewari (Tropical Animal Health and Production, 2012)

Carbon footprint: current methods of estimation - Divya Pandey; Madhoolika Agrawal; Jai Shanker Pandey (Environmental Monitoring and Assessment, 2011)